Perbandingan Skala Nyeri Pasien Kista Endometriosis Dan Adenomiosis Sebelum Operasi, Setelah Operasi Dan Setelah Pemberian GNRH Analog - Marhenriyanto, Wahyuridistia; Hendry, Dedy (Fakultas Kedokteran Universitas Andalas, 2020)
Background: Endometriosis is the growth of the epithelium and endometrial glands outside the uterine cavity. In endometriosis there is a process of neurogenesis and angiogenesis. The degree of endometriosis pain depends on the depth of endometrial implant infiltration in nerve fibers and / or neurogenesis. Operative action and postoperative hormone therapy are the main choices for preventing recurrence and reducing pain complaints.Purpose: to determine the comparison of pain scales of patients with endometriosis before surgery, after surgery and after administration of GnRH analogues.Method: This study was an observational analytic with a retrospective cohort design in the Obstetrics and Gynecology Clinic of RSUP Dr. M. Djamil Padang in June 2017 to January 2018. The sample size were of 35 people with inclusion and exclusion criteria. The inclusion criteria were the diagnosis of endometriosis (endometriosis cysts and adenomyosis) from ultrasonography and anatomical pathology, had surgery and received analogue GnRH injection three times. Exclusion criteria were not proven endometriosis, hysterectomy surgery, using analgesics and not following analogue GnRH injection procedures. The pain scale is assessed by the Wong-Baker Faces Pain Rating Scale. The pain scale is assessed during menstruation before surgery, first menstruation after surgery and first menstruation after three analogues of GnRH injections. Data analysis using SPSS version 22, where univariate analysis is used to see the characteristics of respondents and bivariate analysis using Wilcoxon Test. Statistical test results were significant if p <0.05.Result: Based on the Wilcoxon statistical test results obtained p value = 0.0001 (p value <0.05) which can be concluded that there is a significant reduction in the pain of endometriosis of patients after surgery compared to before surgery.Conclusion: There was a significant decrease in pain in endometriosis patients before surgery.Keywords: Endometriosis, Adenomyosis, Pain Scale, GnRH anaologist